"An Arena for Sharing": Exploring the Joint Involvement of Patients and Their Relatives in a Cancer Rehabilitation Intervention Study. Issue 2 (March 2015) - la Cour, Karen; Ledderer, Loni; Hansen, Helle Ploug
Abstract : Background: Despite an increasing focus on cancer rehabilitation programs, there is limited knowledge about the experiences of residential rehabilitation focusing on both the patients and their relatives. Objective: The aim of this study was to explore the experienced benefits of the joint involvement of patients and their relatives in a 5-day residential cancer rehabilitation course, provided as part of a larger intervention study in Denmark. Methods: Ethnographic fieldwork, consisting of participant observations and informal conversations, was conducted with 20 individuals (10 patients and 10 relatives). In-depth interviews were conducted in the participants' homes 1 month after the rehabilitation course. Data were analyzed by a constant comparative method. Results: Residential rehabilitation course was identified to serve as an "arena for sharing, " underpinned by 3 dimensions of sharing: sharing cancer experiences, sharing strategies, and sharing mutual care. Conclusion: Sharing in residential rehabilitation is experienced as useful for cancer patients and their relatives, to validate cancer-related strategies and strengthen mutual understanding within relationships. Implications for Practice: The results can guide the development of cancer rehabilitation to involve patients and their relatives and provide opportunity for sharing and empowerment on individual as well as couple and group levels.